Eco-humanist Tourism Perspective Towards Sustainability: The Case of Dusun Semilir, Indonesia (Universitas Negeri Semarang, 2022)
A tourist destination designed through the concept of eco-park, Dusun Semilir is one of the environmentally friendly tourist destinations in Semarang. However, the design implementation does not consider the humanist aspects, especially for tourists with limitations (parents and children), who are unable to access. This study aims to provide perspective on a tourist destination that uses the concept of ecotourism as well as combines with humanist architecture, to ensure that environmental relationship with humans remains in synergy. A qualitative method was used to explore phenomena and problems that occur in study objects to produce ecological and universal design concepts. The humanist concept needs to be borrowed to complement the ecotourism concept for the architects and related stakeholders to plan a tourist destination from two perspectives of the concept. We argue that the eco-humanist tourism perspective provides an understanding that a tourist destination is successful when the fulfillment of human needs is met without harming the environment, social, culture, economy of the tourist destination.